Karakteristik Campuran AC-WC Menggunakan Bahan Tambah Limbah Ban Bekas - Owen Irianto Bessoran; Alpius; Olan Jujun Sanggaria (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The problem of the quality of the asphalt mixture, especially on the surface layer, is a matter that really needs to be considered because a poor asphalt mixture will cause the surface layer on the road to be damaged quickly or not in accordance with the expected service period. This research was conducted to test the AC-WC mixture with added waste tires. The research methodology uses the Conventional Marshall method to obtain the characteristics of the AC-WC mixture and Marshall Immersion to obtain the Marshall Residual Stability value. The results show that the characteristics of the AC-WC mixture meet the 2018 Highways Specifications. The results of the Marshall Immersion test with an optimum 4% used tire content obtained a Marshall Stability value of 94.64% and the effect of adding used tire rubber will make the cavities in the mixture smaller thus the mixture can be resistant to water.